Posted by
**Dragonfly** on
.

Solve for x:

5/x+6+2/x^2+7x+6=3/x+1

5/x+5+2/(x+6)(x+1)=3/x+1

5(x+6)(x+1)/x+6+2(x+6)(x+1)/(x+6)(x1)=3(x+6)(x+1)/x+1

5(x+1)+2=3(x+6)

5x+5+2=3x+18

5x+7=3x+18

2x=11

x=11/2 or 5 1/2

is my method correct? and I need assitance checking my answer. Thanks for your help!

You need to use more parentheses to clarify your problem. I don't see how you went from a constant of 6 to 5 in the first two steps:

5/x+6+ 2/(x^2+7x+6)= 3/(x+1)

5/x+5+ 2/(x+6)(x+1) =3/(x+1)

You seem to have left out "+" in the x1 term of the third equation.

It's too full of typos to decipher, but most of your steps seem correctly done.